Maqashid Syariah-Based Analysis of Social Responsibility Implementation in Islamic Banking - Khofifah Nurandini Siregar; Sugianto Sugianto; Yenni Samri Juliati Nasution (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
This study analyzes the implementation of social responsibility programs in Islamic banking through the lens of maqashid sharia. Employing a qualitative case study design, data were collected via interviews, documentation, and literature review. The findings reveal that social responsibility initiatives are manifested through the management of social and charitable funds oriented toward community welfare and sharia values. Programs include educational support, religious activities, social assistance, disaster relief, and other community-based initiatives. From the maqashid sharia perspective, these practices reflect the principles of hifz al-din, hifz al-nafs, hifz al-aql, and hifz al-nasl. However, the principle of hifz al-mal remains underdeveloped due to the absence of productive and sustainable economic empowerment programs. Strengthening community economic empowerment and establishing robust monitoring and evaluation mechanisms are essential to optimize the maqashid sharia-based implementation of social responsibility in Islamic banking. This study contributes to the discourse on aligning Islamic banking practices with maqashid sharia by highlighting both achievements and areas requiring improvement, offering insights for policy development and institutional practice.